2020
DOI: 10.1371/journal.pone.0239196
|View full text |Cite
|
Sign up to set email alerts
|

Lower DNA methylation levels in CpG island shores of CR1, CLU, and PICALM in the blood of Japanese Alzheimer’s disease patients

Abstract: The aim of the present study was to (1) investigate the relationship between late-onset Alzheimer's disease (AD) and DNA methylation levels in six of the top seven AD-associated genes identified through a meta-analysis of recent genome wide association studies, APOE, BIN1, PICALM, CR1, CLU, and ABCA7, in blood, and (2) examine its applicability to the diagnosis of AD. We examined methylation differences at CpG island shores in the six genes using Sanger sequencing, and one of two groups of 48 AD patients and 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…A number of other recent studies also observed hypomethylated CpGs in the blood of AD patients. For example, Fransquet et al (2020) 8 observed the majority of differentially methylated CpGs between dementia cases at diagnosis and controls in their study also had lower methylation levels in the cases; Madrid et al (2018) 12 discovered hypomethylated CpGs on the B3GALT4 and ZADH2 genes in patients with late-onset AD; Mitsumori et al (2020) 13 identified and replicated lower DNA methylation levels in CpG island shores of CR1, CLU , and PICALM genes in the blood of Japanese AD patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of other recent studies also observed hypomethylated CpGs in the blood of AD patients. For example, Fransquet et al (2020) 8 observed the majority of differentially methylated CpGs between dementia cases at diagnosis and controls in their study also had lower methylation levels in the cases; Madrid et al (2018) 12 discovered hypomethylated CpGs on the B3GALT4 and ZADH2 genes in patients with late-onset AD; Mitsumori et al (2020) 13 identified and replicated lower DNA methylation levels in CpG island shores of CR1, CLU , and PICALM genes in the blood of Japanese AD patients.…”
Section: Discussionmentioning
confidence: 96%
“…Most recently, it was shown that DNA methylation changes could be detected in blood at least three years before the onset of dementia symptoms 8 . In particular, blood methylation levels at several candidate loci 9-13 , such as the COASY, HOXB6 , and APP genes, were significantly different between AD patients and healthy controls.…”
Section: Introductionmentioning
confidence: 95%
“…APOE is the gene that was first associated with the development of the late form [ 12 ] compared to other predisposing genes that have been described. These include genes involved in neuroinflammation (such as TREM2, TYROBP, and CD33) [ 13 , 14 , 15 ], memory (CR1, PICALM, and BIN1) [ 16 , 17 , 18 ], and lipid metabolism (ABCA7 and CLU) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further recognize that the sequence differences between the two APOEε4 backgrounds could also influence methylation activity in this region. Although differences in methylation between APOEε4 and the other APOE statuses has been studied [21][22][23]50 , the effect of different ancestral backgrounds has not been fully assessed 51 . Preliminary inhouse comparison of CpG methylation in the subTAD on African versus European APOEε4 haplotypes identified one methylation site with lower methylation levels on European versus African background at the 5'end of fragment 10 (unpublished data).…”
Section: Discussionmentioning
confidence: 99%